An fMRI study investigating effects of conceptually related sentences on the perception of degraded speech. (June 2016) - Guediche, Sara; Reilly, Megan; Santiago, Carolina; Laurent, Patryk; Blumstein, Sheila E.
Abstract: Prior research has shown that the perception of degraded speech is influenced by within sentence meaning and recruits one or more components of a frontal–temporal–parietal network. The goal of the current study is to examine whether the overall conceptual meaning of a sentence, made up of one set of words, influences the perception of a second acoustically degraded sentence, made up of a different set of words. Using functional magnetic resonance imaging (fMRI), we presented an acoustically clear sentence followed by an acoustically degraded sentence and manipulated the semantic relationship between them: Related in meaning (but consisting of different content words), Unrelated in meaning, or Same. Results showed that listeners' word recognition accuracy for the acoustically degraded sentences was significantly higher when the target sentence was preceded by a conceptually related compared to a conceptually unrelated sentence. Sensitivity to conceptual relationships was associated with enhanced activity in middle and inferior frontal, temporal, and parietal areas. In addition, the left middle frontal gyrus (LMFG), left inferior frontal gyrus (LIFG), and left middle temporal gyrus (LMTG) showed activity that correlated with individual performance on the Related condition. The superior temporal gyrus (STG) showed increased activation in the Same condition suggesting that it is sensitive to perceptual similarity rather than the integration of meaning between the sentence pairs. A fronto-temporo-parietal network appears to consolidate information sources across multiple levels of language (acoustic, lexical, syntactic, semantic) to build, and ultimately integrate conceptual information across sentences and facilitate the perception of a degraded speech signal. However, the nature of the sources of information that are available differentially recruit specific regions and modulate their activity within this network. Implications of these findings for the functional architecture of the network are considered.